Adipose tissue derived bacteria are associated with inflammation in obesity and type 2 diabetes - Massier, Lucas; Chakaroun, Rima; Tabei, Shirin; Crane, Alyce; Didt, Konrad David; Fallmann, Jörg; von Bergen, Martin; Haange, Sven-Bastiaan; Heyne, Henrike; Stumvoll, Michael; Gericke, Martin; Dietrich, Arne; et al. (Gut, 2020)
ObjectiveBacterial translocation to various organs including human adipose tissue (AT) due to increased intestinal permeability remains poorly understood. We hypothesised that: (1) bacterial presence is highly tissue specific and (2) related in composition and quantity to immune inflammatory and metabolic burden.DesignWe quantified and sequenced the bacterial 16S rRNA gene in blood and AT samples (omental, mesenteric and subcutaneous) of 75 subjects with obesity with or without type 2 diabetes (T2D) and used catalysed reporter deposition (CARD) – fluorescence in situ hybridisation (FISH) to detect bacteria in AT.ResultsUnder stringent experimental and bioinformatic control for contaminants, bacterial DNA was detected in blood and omental, subcutaneous and mesenteric AT samples in the range of 0.1 to 5 pg/µg DNA isolate. Moreover, CARD-FISH allowed the detection of living, AT-borne bacteria. Proteobacteria and Firmicutes were the predominant phyla, and bacterial quantity was associated with immune cell infiltration, inflammatory and metabolic parameters in a tissue-specific manner. Bacterial composition differed between subjects with and without T2D and was associated with related clinical measures, including systemic and tissues-specific inflammatory markers. Finally, treatment of adipocytes with bacterial DNA in vitro stimulated the expression of TNFA and IL6.ConclusionsOur study provides contaminant aware evidence for the presence of bacteria and bacterial DNA in several ATs in obesity and T2D and suggests an important role of bacteria in initiating and sustaining local AT subclinical inflammation and therefore impacting metabolic sequelae of obesity.